Preparation method of PEDOT powder with high conversion rate

By introducing 3-HPS additives in the preparation process of PEDOT powder and controlling the reaction conditions, the problems of many impurities, complex processes, unstable conductivity and low conversion rates in the prior art are solved, and high conductivity is achieved PEDOT powder preparation with high conversion rate and high conversion rate is suitable for industrial production.

CN119409948AActive Publication Date: 2025-02-11WUHAN PINESTONE TECHNOLOGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411690331.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In the prior art, the preparation of PEDOT powder has problems such as a large number of impurities, complex production process, unstable conductivity and low conversion rate.

Method used

During the polymerization of water-based suspension precipitation, trihydroxypropylsulfonic acid (3-HPS) additive is introduced. By adjusting the dosage of 3-HPS and controlling the reaction temperature, PEDOT powder preparation with high conductivity and high conversion is achieved.

Benefits of technology

The conversion rate of PEDOT powder is significantly improved to reach 98.7%, and the PEDOT powder prepared has a high conductivity, all of which can reach the order of 100S/cm, and the product has higher purity, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409948A_ABST
    Figure CN119409948A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of conductive macromolecules, and particularly relates to a preparation method of high-conversion-rate PEDOT powder. 3-HPS is used as an additive, and preparation of high-conductivity, high-conversion-rate and high-purity PEDOT powder is realized by adjusting the use amount of 3-HPS. The method is simple to operate, few in raw material variety and low in energy consumption, the preparation method is good in repeatability, and the PEDOT product is stable in performance and high in conductivity and has practical commercial significance for industrial mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive polymers, and more specifically, relates to a method for preparing high-conversion-rate PEDOT powder. Background Art

[0002] In 1988, Bayer of Germany submitted an invention patent for EDOT (3,4-ethylenedioxythiophene), and the performance of polythiophene was officially broken through. The PEDOT obtained by Bayer through the polymerization reaction of ferric chloride showed unparalleled high conductivity and stability. Subsequently, Bayer combined the polyanions corresponding to aqueous polystyrene sulfonic acid (PSS) with positively charged doped PEDOT counterions to form a PEDOT:PSS complex, which solved the solubility problem of PEDOT and opened the door to the commercialization of PEDOT. Nowadays, PEDOT and its derivative functional materials have emerged in large numbers and are widely used in hole transport layers in solar cells and OLEDs, biomedicine, thermoelectric materials, electrode materials and supercapacitors, electromagnetic protection and antistatic materials.

[0003] At present, commercialized PEDOT products are mainly PEDOT:PSS inks, which have the problems of single usage, low conductivity, poor processability, and few effective conductive components. Compared with inks, conductive powders have advantages such as higher conductivity, wider application range, stronger processability, and simple storage, and have great commercial prospects. However, it cannot be ignored that powder preparation still has many problems such as unstable conductivity, low conversion rate, complex raw material use, and immature preparation process. Summary of the invention

[0004] In view of the defects of the prior art, the present invention provides a method for preparing PEDOT powder with high conversion rate and conductivity. By introducing trihydroxypropyl sulfonic acid (3-HPS) additive in the water-based suspension precipitation polymerization process, the technical problems existing in the prior art PEDOT powder preparation method, such as a large number of impurity types, complex production process, unstable conductivity, and low PEDOT conversion rate, are solved.

[0005] To achieve the above object, the present invention provides a method for preparing PEDOT powder, comprising the following steps:

[0006] (1) mixing EDOT monomer, 3-HPS additive and water and stirring and dispersing the mixture to obtain an EDOT dispersion;

[0007] (2) Mixing the EDOT dispersion of step (1) with an aqueous solution of ferric chloride as an oxidant, stirring and reacting at room temperature for 20-30 hours, then heating the temperature to 48-55° C. and stirring and reacting for 70-80 hours, separating the solid and the liquid after the reaction, washing and drying the separated solid phase, and obtaining the PEDOT powder.

[0008] Preferably, the molar ratio of the EDOT monomer to the 3-HPS additive in step (1) is 1:(0.1-1.2).

[0009] Preferably, the concentration of EDOT in the EDOT dispersion in step (1) is 1-5 wt %.

[0010] Preferably, the molar ratio of the oxidant ferric chloride to the EDOT monomer in step (2) is (2-4):1, more preferably (2-3):1.

[0011] Preferably, in step (2), the aqueous solution of ferric chloride is added to the EDOT dispersion at one time, or the aqueous solution of ferric chloride is added dropwise to the EDOT dispersion.

[0012] Preferably, in step (2), the EDOT dispersion of step (1) is mixed with an aqueous solution of ferric chloride as an oxidant, and the mixture is stirred and reacted at room temperature for 20-30 hours, and then heated to 48-52° C. and stirred and reacted for 70-80 hours.

[0013] Preferably, in step (2), the solid phase obtained by solid-liquid separation is washed alternately in water and ethanol.

[0014] Preferably, the drying in step (2) is freeze drying for 36-72 hours.

[0015] Preferably, the conductivity of the PEDOT powder is between 10 0 S / cm order of magnitude; its conversion rate is greater than 93%.

[0016] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0017] 1. The present invention proposes a water-based suspension precipitation reaction preparation method for PEDOT powder, which can significantly improve the reaction conversion rate by introducing 3-HPS additive during the preparation process compared with the case without adding 3-HPS additive.

[0018] 2. The PEDOT powder prepared by the preparation method of the present invention has high conductivity, which can reach 10 0 Since 3-HPS is a small molecule additive that is easily soluble in water, it is easy to remove during the cleaning process, thus making the product powder have a higher purity.

[0019] 3. The method of PEDOT suspension precipitation polymerization described in the present invention uses 3-HPS as an additive, adjusts the amount of 3-HPS, and controls the temperature of the reaction process to achieve the preparation of high conductivity, high conversion rate, and high purity PEDOT powder. This method is simple to operate, has a small number of raw materials, and has low energy consumption. The preparation method has good repeatability, and the PEDOT product has stable performance and high conductivity, which has practical commercial significance for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the reaction route diagram of PEDOT polymerization of the present invention;

[0021] Figure 2 is a process flow chart of the preparation method of the present invention;

[0022] Figure 3 This is a photo of the PEDOT powder prepared in Example 1 of the present invention;

[0023] Figure 4 X-ray photoelectron spectra of the PEDOT products prepared in Comparative Example 1 and Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0025] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0026] Additionally, references throughout this specification to "one embodiment," "one embodiment," "an example," or similar language indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment of the present invention. Thus, appearances of the phrase "in one embodiment," "in one embodiment," and similar language throughout this specification may, but do not necessarily, all refer to the same embodiment.

[0027] The present invention provides a method for preparing PEDOT powder, comprising the following steps:

[0028] (1) mixing EDOT monomer, 3-HPS additive and water and stirring and dispersing the mixture to obtain an EDOT dispersion;

[0029] (2) Mixing the EDOT dispersion of step (1) with an aqueous solution of ferric chloride as an oxidant, stirring and reacting at room temperature for 20-30 hours, then heating the temperature to 48-55° C. and stirring and reacting for 70-80 hours, separating the solid and the liquid after the reaction, washing and drying the separated solid phase, and obtaining the PEDOT powder.

[0030] In some embodiments, the molar ratio of the EDOT monomer and the 3-HPS additive in step (1) is 1:(0.1-1.2), preferably 1:(0.2-1.1). The concentration of EDOT in the EDOT dispersion in step (1) is 1-5wt%. The molar ratio of the oxidant ferric chloride to the EDOT monomer in step (2) is (2-4):1, preferably (2-3):1, and more preferably 2.5:1; the ferric chloride in the present invention can be ferric chloride hexahydrate or anhydrous ferric chloride.

[0031] In some embodiments, in step (2), the aqueous solution of ferric chloride is added to the EDOT dispersion at one time, or the aqueous solution of ferric chloride is added dropwise to the EDOT dispersion. In a preferred embodiment, the oxidant ferric chloride solution is added dropwise within 2 hours; under lower dropping temperature conditions, the dropping speed can be appropriately increased.

[0032] During the dropwise addition of the oxidant ferric chloride solution, the temperature in the reactor is generally controlled at around 25°C and not lower than 10°C; of course, in some cases, the temperature in the reactor can also be appropriately lowered (not lower than 10°C) to reduce the polymerization rate of EDOT during the dropwise addition process and prevent negative effects such as uneven particle size caused by local polymerization.

[0033] In a preferred embodiment, step (2) is to mix the EDOT dispersion of step (1) with an aqueous solution of ferric chloride as an oxidant, and stir the mixture at room temperature (20-30° C.) for 20-30 hours, and then heat the mixture to 48-52° C. for 70-80 hours.

[0034] In some embodiments, the solid phase obtained by solid-liquid separation in step (2) is washed alternately in water and ethanol. The drying is freeze drying for 36-72 hours.

[0035] In the preparation method of the present invention, no additives other than 3-HPS are added, and the conductivity of the prepared PEDOT powder is between 10 0 S / cm order of magnitude; its conversion rate is greater than 93%.

[0036] PEDOT powder is prepared based on water-based suspended precipitation polymerization. The higher the conversion rate of the polymerization reaction of EDOT monomer, the higher the production efficiency. It has important commercial significance for the production of PEDOT. Therefore, the pursuit of higher conversion rate has become one of the important goals of PEDOT production. However, the highest conversion rate in the preparation process of the traditional method is about 90%, but it is difficult to further improve the reaction conversion rate. The present invention accidentally discovered that the introduction of 3-HPS additives in the precipitation polymerization process can increase its conversion rate to 98.7%, which is close to 100%. Moreover, the conductivity of the prepared PEDOT powder is high, on the order of 10 0 S / cm.

[0037] In some embodiments, the water described in the present invention is one or more of ultrapure water, deionized water, double distilled water, pure water, and distilled water.

[0038] The method of PEDOT suspension precipitation polymerization described in the present invention introduces a 3-HPS additive and adjusts the dosage of 3-HPS to achieve the preparation of PEDOT powder with high conductivity and high conversion rate. This method is simple to operate, has a small number of raw materials, and has low energy consumption. The preparation method has good repeatability, and the PEDOT product has stable performance and high conductivity, which has practical commercial significance for industrial mass production.

[0039] During the preparation method of the present invention, as the reaction continues, the solid product increases, the solid content of the system rises, becomes viscous, and the fluidity deteriorates, which is not conducive to the continued progress of the reaction. It is inferred that the additive 3-HPS may play a certain dispersing role, can prevent the newly generated PEDOT solid particles from agglomerating to form large particles, significantly improve the fluidity of the reaction system, reduce the viscosity of the reaction system, avoid the adverse effects of excessive viscosity on the polymerization process, improve the reaction degree of PEDOT, and improve the conversion rate of PEDOT and the efficiency of production and preparation. At the same time, the 3-HPS additive can also effectively reduce the particle size of PEDOT particles, making the particles finer, the particle size distribution narrower, and the contact with each other closer, thereby improving its conductivity. In addition, since the 3-HPS additive is a small molecule, it can be easily cleaned and removed from the product, making the purity of the PEDOT powder product higher.

[0040] The present invention adjusts the amount of 3-HPS to stably prepare a conductive 0 S / cm order of PEDOT powder, and its conversion rate increased to a large extent.

[0041] In some embodiments, Figure 1 and Figure 2 As shown, the preparation method specifically comprises the following steps:

[0042] S1. Dispersion of EDOT: a certain amount of distilled water is added to a reaction container, and EDOT monomer and a certain amount of 3-HPS are added. The EDOT monomer is fully dispersed by continuous stirring to obtain a slightly yellowish milky EDOT dispersion.

[0043] S2. Adding ferric chloride dropwise: Take a certain amount of ferric chloride hexahydrate and dissolve it in a certain amount of distilled water. Keep stirring in the reaction container and add the ferric chloride solution into the reaction container at room temperature (25° C.).

[0044] S3. Polymerization of EDOT: Keep stirring continuously and react at room temperature for 24 hours after the addition is completed; then raise the temperature to 50°C and react for 72 hours.

[0045] S4. Collection, washing and drying of PEDOT: After the reaction is completed, the reaction liquid is separated into solid and liquid, leaving a solid product. The product is repeatedly rinsed with distilled water and anhydrous ethanol several times. After the rinsing is completed, the solid product is dispersed in distilled water or anhydrous ethanol, and washed several times by ultrasonic heating cleaning until the filtrate is clear and transparent. After the cleaning is completed, the solid product is freeze-dried to obtain PEDOT powder.

[0046] In some embodiments, step S4 uses distilled water and anhydrous ethanol to alternately rinse the product several times. After the rinsing is completed, the solid product is fully dispersed in anhydrous ethanol, and the PEDOT solid is washed by ultrasonic heating cleaning, each time the temperature is set to 50-60°C, and the ultrasound is performed for 20-30 minutes. After the ultrasonic cleaning is completed, the PEDOT solid product is separated by filtration, and the cleaning is repeated several times, and then the distilled water is used to wash several times in the same way. During this period, ethanol and distilled water can also be used to alternately wash in this way. After the cleaning is completed, the solid product is placed in a freeze drying box and freeze-dried for 48-72 hours to obtain PEDOT powder.

[0047] The PEDOT powder prepared by the preparation method of the present invention has higher electrical conductivity. Compared with traditional water-based precipitation polymerization, the PEDOT powder prepared by this method has higher purity, higher effective conductive components and good processability.

[0048] The following are specific embodiments:

[0049] Example 1

[0050] S1. Dissolution of EDOT: 5 g EDOT and 1.68 g 3-HPS (0.34 times the molar number of EDOT) were added to a 250 mL conical flask, and a certain amount of distilled water was added to prepare 120 mL EDOT dispersion. The conical flask was fixed in a water bath magnetic stirrer, and stirring was started for 1 hour to obtain a uniformly dispersed EDOT dispersion.

[0051] S2. Addition of ferric chloride solution: Take 23.76 g of ferric chloride hexahydrate, dissolve it in a certain amount of distilled water, prepare 130 mL of ferric chloride aqueous solution, and add it dropwise to the reaction solution within 2 hours at room temperature (near 25° C.).

[0052] S3. Polymerization of EDOT: After the ferric chloride solution was added dropwise, the reaction was maintained at room temperature (25°C, the same below) for 24 hours. After reacting at room temperature for 24 hours, the reaction solution was heated from room temperature to 50°C, and then reacted for 72 hours.

[0053] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. After washing the product alternately with distilled water and anhydrous ethanol for several times, transfer the PEDOT solid product to a 500mL beaker, add 200mL of anhydrous ethanol, set the ultrasonic time to 30min, and the ultrasonic temperature to 60℃ for ultrasonic cleaning. After completion, use a sand core funnel to filter and separate the solid product. Continue to use anhydrous ethanol and distilled water to alternately ultrasonically clean several times until the filtrate is clear and transparent.

[0054] After washing, the solid product was placed in a freeze drying oven and freeze-dried for 72 hours. After drying, the obtained PEDOT solid product was placed in an agate mill and crushed into fine powder, thus obtaining PEDOT powder (such as Figure 3 shown).

[0055] Prepared PEDOT powder test:

[0056] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 6.763×10 0 S / cm.

[0057] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows

[0058]

[0059] Where: m PEDOT is the mass of the collected product; m EDOT is the mass of the added EDOT monomer. After drying, the PEDOT solid was collected and the conversion rate of PEDOT was calculated according to this formula to be 93.4%.

[0060] Example 2

[0061] S1. Dissolution of EDOT: 5 g EDOT and 3.30 g 3-HPS (0.67 times the molar number of EDOT) were added to a 250 mL conical flask, and a certain amount of distilled water was added to prepare 120 mL EDOT dispersion. The conical flask was fixed in a water bath magnetic stirrer, and stirring was started for 1 hour to obtain a uniformly dispersed EDOT dispersion.

[0062] S2. Addition of ferric chloride solution: Take 23.76 g of ferric chloride hexahydrate, dissolve it in a certain amount of distilled water, prepare 130 mL of ferric chloride aqueous solution, and add it dropwise to the reaction solution within 2 hours at room temperature (near 25° C.).

[0063] S3, EDOT polymerization: After the ferric chloride solution is added dropwise, the reaction is maintained at room temperature for 24 hours; after reacting at room temperature for 24 hours, the reaction solution is heated from room temperature to 50°C, and then reacted for 72 hours after the temperature is raised to 50°C;

[0064] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. After washing the product alternately with distilled water and anhydrous ethanol for several times, transfer the PEDOT solid product to a 500mL beaker, add 200mL of anhydrous ethanol, set the ultrasonic time to 30min, and the ultrasonic temperature to 60℃ for ultrasonic cleaning. After completion, use a sand core funnel to filter and separate the solid product. Continue to use anhydrous ethanol and distilled water to alternately ultrasonically clean several times until the filtrate is clear and transparent.

[0065] After washing, the solid product was placed in a freeze drying oven and freeze-dried for 72 hours. After drying, the obtained PEDOT solid product was placed in an agate mill and crushed into fine powder, thus obtaining PEDOT powder.

[0066] Prepared PEDOT powder test:

[0067] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 5.091×10 0 S / cm.

[0068] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows

[0069]

[0070] Where: m PEDOT is the mass of the collected product; m EDOT is the mass of the added EDOT monomer. After drying, the PEDOT solid was collected and the conversion rate of PEDOT was calculated according to this formula to be 95.8%.

[0071] Example 3

[0072] S1. Dissolution of EDOT: Take 5g EDOT and 5.18g 3-HPS (1.05 times the molar number of EDOT) and add them into a 250mL conical flask, and pour a certain amount of distilled water to prepare 120mL EDOT dispersion. Fix the conical flask in a water bath magnetic stirrer, start stirring, and stir for 1 hour to obtain a uniformly dispersed EDOT dispersion.

[0073] S2. Addition of ferric chloride solution: Take 23.76 g of ferric chloride hexahydrate, dissolve it in a certain amount of distilled water, prepare 130 mL of ferric chloride aqueous solution, and add it dropwise to the reaction solution within 2 hours at room temperature (near 25° C.).

[0074] S3, EDOT polymerization: After the ferric chloride solution is added dropwise, the reaction is maintained at room temperature for 24 hours; after reacting at room temperature for 24 hours, the reaction solution is heated from room temperature to 50°C, and then reacted for 72 hours after the temperature is raised to 50°C;

[0075] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. After washing the product alternately with distilled water and anhydrous ethanol for several times, transfer the PEDOT solid product to a 500mL beaker, add 200mL of anhydrous ethanol, set the ultrasonic time to 30min, and the ultrasonic temperature to 60℃ for ultrasonic cleaning. After completion, use a sand core funnel to filter and separate the solid product. Continue to use anhydrous ethanol and distilled water to alternately ultrasonically clean several times until the filtrate is clear and transparent.

[0076] After washing, the solid product was placed in a freeze drying oven and freeze-dried for 72 hours. After drying, the obtained PEDOT solid product was placed in an agate mill and crushed into fine powder, thus obtaining PEDOT powder.

[0077] Prepared PEDOT powder test:

[0078] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 5.005×10 0 S / cm.

[0079] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows

[0080]

[0081] Where: m PEDOT is the mass of the collected product; m EDOT is the mass of the added EDOT monomer. After drying, the PEDOT solid was collected and the conversion rate of PEDOT was calculated according to this formula to be 97.8%.

[0082] Comparative Example 1

[0083] S1. Dissolution of EDOT: Take 5g of EDOT and add it to a 250mL Erlenmeyer flask, add a certain amount of distilled water, and prepare it into 120mL EDOT dispersion. Fix the Erlenmeyer flask in a water bath magnetic stirrer, start stirring, and stir for 1 hour to obtain a uniformly dispersed EDOT dispersion.

[0084] S2. Addition of ferric chloride solution: Take 23.76 g of ferric chloride hexahydrate, dissolve it in a certain amount of distilled water, prepare 130 mL of ferric chloride aqueous solution, and add it dropwise to the reaction solution within 2 hours at room temperature (near 25° C.).

[0085] S3, EDOT polymerization: After the ferric chloride solution is added dropwise, the reaction is maintained at room temperature for 24 hours; after reacting at room temperature for 24 hours, the reaction solution is heated from room temperature to 50°C, and then reacted for 72 hours after the temperature is raised to 50°C;

[0086] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. After washing the product alternately with distilled water and anhydrous ethanol for several times, transfer the PEDOT solid product to a 500mL beaker, add 200mL of anhydrous ethanol, set the ultrasonic time to 30min, and the ultrasonic temperature to 60℃ for ultrasonic cleaning. After completion, use a sand core funnel to filter and separate the solid product. Continue to use anhydrous ethanol and distilled water to alternately ultrasonically clean several times until the filtrate is clear and transparent.

[0087] After washing, the solid product was placed in a freeze drying oven and freeze-dried for 72 hours. After drying, the obtained PEDOT solid product was placed in an agate mill and crushed into fine powder, thus obtaining PEDOT powder.

[0088] Prepared PEDOT powder test:

[0089] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 6.805×10 0 S / cm.

[0090] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows

[0091]

[0092] Where: m PEDOT is the mass of the collected product; m EDOT is the mass of the added EDOT monomer. After drying, the PEDOT solid was collected, and the conversion rate of PEDOT was calculated according to this formula to be 92%.

[0093] Comparative Example 2

[0094] S1. Dissolution of EDOT: 5 g EDOT and 1.68 g 3-HPS (0.34 times the molar number of EDOT) were added to a 250 mL conical flask, and a certain amount of distilled water was added to prepare 120 mL EDOT dispersion. The conical flask was fixed in a water bath magnetic stirrer, and stirring was started for 1 hour to obtain a uniformly dispersed EDOT dispersion.

[0095] S2. Addition of ferric chloride: Take 23.76 g of ferric chloride hexahydrate, dissolve it in a certain amount of distilled water to prepare 130 mL of ferric chloride aqueous solution, and add it dropwise to the reaction solution at room temperature (25° C.) for 2 hours.

[0096] S3, EDOT polymerization: after the ferric chloride solution is added dropwise, the reaction is maintained at room temperature for 24 hours; after reacting at room temperature for 24 hours, the reaction solution is heated from room temperature to 40°C, and then reacted for 24 hours at 40°C; after reacting at 40°C for 24 hours, the reaction solution is heated from 40°C to 50°C, and then reacted for 48 hours at 50°C;

[0097] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. After washing the product alternately with distilled water and anhydrous ethanol for several times, transfer the PEDOT solid product to a 500mL beaker, add 200mL of anhydrous ethanol, set the ultrasonic time to 30min, and the ultrasonic temperature to 60℃ for ultrasonic cleaning. After completion, use a sand core funnel to filter and separate the solid product. Continue to use anhydrous ethanol and distilled water to alternately ultrasonically clean several times until the filtrate is clear and transparent.

[0098] After washing, the solid product was placed in a freeze drying oven and freeze-dried for 72 hours. After drying, the obtained PEDOT solid product was placed in an agate mill and crushed into fine powder, thus obtaining PEDOT powder.

[0099] Prepared PEDOT powder test:

[0100] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 2.543×10 0 S / cm.

[0101] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows

[0102]

[0103] Where: m PEDOT is the mass of the collected product; m EDOT is the mass of the added EDOT monomer. After drying, the PEDOT solid was collected and the conversion rate of PEDOT was calculated to be 79.2% according to this formula.

[0104] Comparative Example 3

[0105] S1. Dissolution of EDOT: 5 g EDOT and 3.30 g 3-HPS (0.67 times the molar number of EDOT) were added to a 250 mL conical flask, and a certain amount of distilled water was added to prepare 120 mL EDOT dispersion. The conical flask was fixed in a water bath magnetic stirrer, and stirring was started for 1 hour to obtain a uniformly dispersed EDOT dispersion.

[0106] S2. Addition of ferric chloride: Take 23.76 g of ferric chloride hexahydrate, dissolve it in a certain amount of distilled water to prepare 130 mL of ferric chloride aqueous solution, and add it dropwise to the reaction solution at room temperature (25° C.) for 2 hours.

[0107] S3, EDOT polymerization: after the ferric chloride solution is added dropwise, the reaction is maintained at room temperature for 24 hours; after reacting at room temperature for 24 hours, the reaction solution is heated from room temperature to 40°C, and then reacted for 24 hours at 40°C; after reacting at 40°C for 24 hours, the reaction solution is heated from 40°C to 50°C, and then reacted for 48 hours at 50°C;

[0108] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. After washing the product alternately with distilled water and anhydrous ethanol for several times, transfer the PEDOT solid product to a 500mL beaker, add 200mL of anhydrous ethanol, set the ultrasonic time to 30min, and the ultrasonic temperature to 60℃ for ultrasonic cleaning. After completion, use a sand core funnel to filter and separate the solid product. Continue to use anhydrous ethanol and distilled water to alternately ultrasonically clean several times until the filtrate is clear and transparent.

[0109] After washing, the solid product was placed in a freeze drying oven and freeze-dried for 72 hours. After drying, the obtained PEDOT solid product was placed in an agate mill and crushed into fine powder, thus obtaining PEDOT powder.

[0110] Prepared PEDOT powder test:

[0111] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 2.234×10 0 S / cm.

[0112] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows

[0113]

[0114] Where: m PEDOT is the mass of the collected product; m EDOT is the mass of the added EDOT monomer. After drying, the PEDOT solid was collected and the conversion rate of PEDOT was calculated to be 81.4% according to this formula.

[0115] Comparative Example 4

[0116] S1. Dissolution of EDOT: Take 5g of EDOT and add it to a 250mL Erlenmeyer flask, add a certain amount of distilled water, and prepare it into 120mL EDOT dispersion. Fix the Erlenmeyer flask in a water bath magnetic stirrer, start stirring, and stir for 1 hour to obtain a uniformly dispersed EDOT dispersion.

[0117] S2. Addition of ferric chloride: Take 23.76 g of ferric chloride hexahydrate, dissolve it in a certain amount of distilled water to prepare 130 mL of ferric chloride aqueous solution, and add it dropwise to the reaction solution at room temperature (25° C.) for 2 hours.

[0118] S3. Polymerization of EDOT: After the addition of ferric chloride solution is completed, the reaction is maintained at room temperature for 24 hours; after reacting at room temperature for 24 hours, the reaction solution is raised from room temperature to 40°C, and then reacted for 24 hours after rising to 40°C; after reacting at 40°C for 24 hours, the reaction solution is raised from 40°C to 50°C, and then reacted for 48 hours after rising to 50°C.

[0119] S4. Collection, washing and drying of PEDOT: After the reaction is completed, use a G6 sand core funnel to filter the reaction solution to obtain a blue-black PEDOT solid. After washing the product alternately with distilled water and anhydrous ethanol for several times, transfer the PEDOT solid product to a 500mL beaker, add 200mL of anhydrous ethanol, set the ultrasonic time to 30min, and the ultrasonic temperature to 60℃ for ultrasonic cleaning. After completion, use a sand core funnel to filter and separate the solid product. Continue to use anhydrous ethanol and distilled water to alternately ultrasonically clean several times until the filtrate is clear and transparent.

[0120] After washing, the solid product was placed in a freeze drying oven and freeze-dried for 72 hours. After drying, the obtained PEDOT solid product was placed in an agate mill and crushed into fine powder, thus obtaining PEDOT powder.

[0121] Prepared PEDOT powder test:

[0122] 1. PEDOT conductivity test method: Pour a certain amount of PEDOT powder into a tableting mold, pressurize to 40mPa and maintain the pressure for 30 minutes. Then take out the PEDOT sheet, measure its thickness and use a four-probe resistivity tester to test its conductivity (the four-probe tester is Japan Mitsubishi MCP-TP610, the test probe is Japan Mitsubishi MCP-TP06P, and the probe calibrator is Japan Mitsubishi RMH311). The test shows that the conductivity of the PEDOT powder is 5.189×10 0 S / cm.

[0123] 2. PEDOT conversion rate test method: The conversion rate calculation formula is as follows

[0124]

[0125] Where: m PEDOT is the mass of the collected product; m EDOT is the mass of the added EDOT monomer. After drying, the PEDOT solid was collected and the conversion rate of PEDOT was calculated to be 60.8% according to this formula.

[0126] The conductivity and conversion rate results of PEDOT powders prepared under different conditions in different embodiments and comparative examples are listed in Table 1.

[0127] As can be seen from Table 1, compared with Example 1, Example 2, Example 3, and Comparative Example 1, after adding 3-HPS, the conductivity remains almost unchanged and is maintained at 10 0 S / cm order of magnitude, with the increase of 3-HPS addition, the conversion rate can be increased to 98.7% at most, which is close to 100%.

[0128] During the experiment, we also tested the possibility of appropriately lowering the reaction temperature in the hope of slowing down the reaction speed and obtaining a higher conductivity, such as Comparative Examples 2, 3, and 4 in Table 1. The temperature of a portion of the reaction was lowered to 40°C. It was found that the temperature reduction was not conducive to the reaction, and the conductivity could be maintained at 10 0 S / cm order of magnitude, but the conversion rate drops significantly, and its industrial production significance is far less than that of the embodiment.

[0129] Table 1 Conductivity and conversion rate results of PEDOT powders prepared in different embodiments and comparative examples

[0130]

[0131] In addition, if Figure 4 As shown (content a, content b, content c and content d correspond to comparative example 1, example 1, example 2 and example 3 respectively), the sulfur element in the products prepared in different examples and comparative examples was analyzed by X-ray photoelectron spectrometer (Thermo SCIENTIFIC; ESCALAB 250Xi). Among them, the sulfur peak of the thiophene ring on the main chain of the product PEDOT should appear near 164eV, which is consistent with the measured spectrum; the sulfur peak of the sulfonate group in 3-HPS should appear near 168.1eV, but in the spectrum, no obvious peak appears near 168.1eV, which indicates that the PEDOT product prepared in the embodiment of the present invention does not contain sulfonate groups, and the residual 3-HPS impurities can be removed more thoroughly by washing.

[0132] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing PEDOT powder, characterized in that: The steps include: (1) mixing EDOT monomer, 3-HPS additive and water and stirring and dispersing the mixture to obtain an EDOT dispersion; (2) Mixing the EDOT dispersion of step (1) with an aqueous solution of ferric chloride as an oxidant, stirring and reacting at room temperature for 20-30 hours, then heating the temperature to 48-55° C. and stirring and reacting for 70-80 hours, separating the solid and the liquid after the reaction, washing and drying the separated solid phase, and obtaining the PEDOT powder.

2. The preparation method according to claim 1, characterized in that The molar ratio of the EDOT monomer to the 3-HPS additive in step (1) is 1:(0.1-1.2).

3. The preparation method according to claim 1, characterized in that: The concentration of EDOT in the EDOT dispersion in step (1) is 1-5wt%.

4. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of the oxidant ferric chloride to the EDOT monomer is (2-4):1, preferably (2-3):

1.

5. The preparation method according to claim 1, characterized in that: Step (2) adding the aqueous solution of ferric chloride into the EDOT dispersion at one time, or adding the aqueous solution of ferric chloride dropwise into the EDOT dispersion.

6. The preparation method according to claim 1, characterized in that: Step (2) The EDOT dispersion of step (1) is mixed with an aqueous solution of ferric chloride as an oxidant, and the mixture is stirred at room temperature for 20-30 hours, and then heated to 48-52° C. and stirred for 70-80 hours.

7. The preparation method according to claim 1, characterized in that: Step (2) The solid phase obtained by solid-liquid separation is washed alternately in water and ethanol.

8. The preparation method according to claim 1, characterized in that: The drying in step (2) is freeze drying for 36-72 hours.

9. The preparation method according to claim 1, characterized in that: The conductivity of the PEDOT powder is 10 0 S / cm order of magnitude; its conversion rate is greater than 93%.

Citation Information

Patent Citations

  • High dispersibility nano-scale poly (3,4-ehtylene dioxythiophene), preparation and use thereof

    CN101407575A

  • Preparation method of low-resistivity low-temperature curing silver paste

    CN117095874A

  • Conductive polymer aqueous solution, and use of the same

    JP2021195437A

  • Poly(3,4-ethylenedioxythiophene)

    US20100282998A1